2017
DOI: 10.1007/s10209-017-0569-1
|View full text |Cite
|
Sign up to set email alerts
|

User preferences for adaptive user interfaces in health information systems

Abstract: Purpose: An adaptive user interface requires identification of user requirements. Interface designers and engineers must understand end-user interaction with the system to improve user interface design. Methods: A combination of interviews and observations are applied for user requirement analysis in health information systems (HIS). Then user preferences are categorized in this paper as either data entry, language and vocabulary, information presentation, or help, warning and feedback. The user preferences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This greatly impedes their adoption in healthcare ( Arnrich et al, 2010 ). A design approach that is driven by a “user-centered” or “participatory design” viewpoint aims to counter this limitation by identifying and incorporating the requirements and end users’ needs at each stage of the design process ( Bergold and Thomas, 2012 ; Sivan et al, 2014 ; Eslami et al, 2018 ). Questionnaires are among the tools that have been developed to identify end-user requirements ( Shah et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…This greatly impedes their adoption in healthcare ( Arnrich et al, 2010 ). A design approach that is driven by a “user-centered” or “participatory design” viewpoint aims to counter this limitation by identifying and incorporating the requirements and end users’ needs at each stage of the design process ( Bergold and Thomas, 2012 ; Sivan et al, 2014 ; Eslami et al, 2018 ). Questionnaires are among the tools that have been developed to identify end-user requirements ( Shah et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…The use of tailoring has been widely used in the area of health communication to reduce task complexity and simplify decision making among different groups of users [15]. However, researchers are beginning to explore how personalization, a form of digital tailoring, can be used to help improve online health search and communication tasks [16-23].…”
Section: Introductionmentioning
confidence: 99%
“…They found that participants who used the guided search felt their search process would improve in the future. Several researchers have also looked at frameworks and models to support adaptive health interfaces [20,22,23] and further work on adaptive interfaces in health [16,21]. These interfaces automatically or semiautomatically change content or information based on knowledge of the user [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature shows that the user-centered approach is required to meet the requirements of intended users (health care professionals, patients, and their caregivers) [ 25 - 27 ]. Although there are mixed findings about the opportunities and benefits of home-based technologies, some studies show that home-based rehabilitation technologies offer interventions that are equivalent to conventional interventions [ 11 ].…”
Section: Discussionmentioning
confidence: 99%